A smart hydrogel patch with high transparency, adhesiveness and hemostasis for all-round treatment and glucose monitoring of diabetic foot ulcers. Issue 30 (22nd July 2022) - Liu, Hou; Li, Zuhao; Che, Songtian; Feng, Yubin; Guan, Lin; Yang, Xinting; Zhao, Yue; Wang, Jincheng; Zvyagin, Andrei V.; Yang, Bai; Lin, Quan
Abstract : A smart transparent and conductive hydrogel patch was engineered for all-round treatment of diabetic foot ulcers, meanwhile, the capacity of glucose monitoring could reflect the blood sugar levels and help to adjust the therapeutic regimen in time. Abstract : The treatment and management of diabetic foot ulcers (DFUs) is a pretty intractable problem for clinical nursing. Urgently, the "Black Box" status of the healing process prevents surgeons from providing timely analysis for more effective diagnosis and therapy of the wound. Herein, we designed a transparent monitoring system to treat and manage the DFUs with blood oozing and hard-healing, which resolved the problem of blind management for the other conductive patches. This system was prepared from a conductive hydrogel patch with ultra-high transparence (up to 93.6%), adhesiveness and hemostasis, which is engineered by assembling in situ formed poly(tannic acid) (PTA)-doped polypyrrole (PPy) nanofibrils in the poly(acrylamide-acrylated adenine) (P(AM-Aa)) polymer networks. Significantly, the high transparent conductive hydrogel patch can monitor the wound-healing status visually and effectively promote the healing of DFUs by accelerating hemostasis, improving communication between cells, preventing wound infection, facilitating collagen deposition, and promoting angiogenesis. In addition, the versatile hydrogel patch could realize indirect blood glucose monitoring by detecting the glucose levels on wounds, and further sense the movements with different magnitudes of human body timely. This research may provide a novel strategy in the design of chronic wound dressings for monitoring and treating the wounds synergistically.